TINDAKAN HUKUM TERHADAP KURIR NARKOBA DILAKUKAN ANAK DIBAWAH UMUR BERDASARKAN UNDANG-UNDANG NARKOTIKA - Fani Nova Silvana (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACTNarcotics abuse no longer looks at age ranging from teenagers, adults to parents. It is not uncommon for narcotics dealers to use underage children to be used as couriers for illegal drugs. Lack of knowledge of narcotics and the inability to refuse and resist, make minors the target of narcotics dealers to distribute narcotics widely and covertly. The problem of this thesis is: 1) how are legal sanctions against underage drug couriers? 2) how to protect the rights of children who become drug couriers?The research methods and techniques used are normative methods and research by means of library research, namely activities carried out by collecting data and studying books that have to do with research and research documents or archives relating to research, namely drug couriers who are still underage. The conclusions in this thesis are 1) the imposition of convictions on children who become drug couriers as stipulated in as stipulated by the types of crimes that can be imposed by child judges in Article 71 paragraph 91) and (2) Law No. 11 of 2012 concerning the Juvenile Justice System must be considered regarding the articles applied in accordance with Law No. 35 of 2009 concerning Narcotics 2) before entering the process of imprisonment of the child against children who become narcotics couriers, there are legal safeguards under the Child Criminal Justice System Law through a restorative justice approach to achieve diversion and based on the discretion from law enforcement. But for children as narcotics couriers, the threat of punishment is more than 7 (seven) years, it is not compulsory for diversion.Keywords: Legal Protection, Courier, Narcotics, Children